Interactions between dietary docosahexaenoic acid and other long-chain polyunsaturated fatty acids on performance and fatty acid retention in post-smolt Atlantic salmon (Salmo salar) - Glencross, Brett; Tocher, Douglas R; Matthew, Chessor; Bell, J Gordon (Fish Physiology and Biochemistry, 2014)
A study with varying dietary inclusion levels (1, 5, 10, 15 and 20 g kg-1) of docosahexaenoic acid (DHA; 22:6n-3) was conducted with post-smolt (111 ± 2.6 g; mean ± S.) Atlantic salmon (Salmo salar) over a 9-week period. In addition to the series of DHA inclusion levels, the study included further diets that had DHA at 10 g kg-1 in combination with either eicosapentaenoic acid (EPA; 20:5n-3) or arachidonic acid (ARA; 20:4n-6), both also included at 10 g kg-1. An additional treatment with both EPA and DHA included at 5 g kg-1 (total of 10 g kg-1 long-chain polyunsaturated fatty acids, LC-PUFA) was also included. After a 9-week feeding period, fish were weighed, and carcass, blood and tissue samples collected. A minor improvement in growth was seen with increasing inclusion of DHA. However, the addition of EPA further improved growth response while addition of ARA had no effect on growth. As with most lipid studies, the fatty acid composition of the whole body lipids generally reflected that of the diets. However, there were notable exceptions to this, and these implicate some interactions among the different LC-PUFA in terms of the fatty acid bio- chemistry in this species. At very low inclusion levels, DHA retention was substantially higher (*250 %) than that at all other inclusion levels (31–58 %). The inclusion of EPA in the diet also had a positive effect on the retention efficiency of DHA. However, EPA retention was highly variable and at low DHA inclusion levels there was a net loss of EPA as this fatty acid was most likely elongated to produce DHA, consistent with increased DHA retention with addi- tional EPA in the diet. Retention of DPA (22:5n-3) was high at low levels of DHA, but diminished with increasing DHA inclusion, similar to that seen with DHA retention. The addition of EPA to the diet resulted in a substantial increase in the efficiency of DPA retention; the inclusion of ARA had the opposite effect. Retention of ARA was unaffected by DHA inclusion, but the addition of either EPA or ARA to the ...